How do English-as-a-foreign-language (EFL) teachers perceive and engage with critical thinking: A systematic review from 2010 to 2020. (March 2022) - Yuan, Rui; Liao, Wei; Wang, Zhaoxuan; Kong, Jialing; Zhang, Yi
Highlights: Teachers recognize the necessity and values of integrating CT in EFL education. Many teachers present partial or misconceived understandings of CT. Teachers use triggering, exposing, guiding, and extending strategies to teach CT. Teachers need courses/programs that provide explicit training on CT instruction. Research fields need more quantitative and action-oriented studies on CT instruction. Abstract: This article presents a critical review of 25 empirical studies on English-as-a-foreign-language (EFL) teachers' perceptions of and engagement with critical thinking (CT) in a wide range of educational contexts from 2010 to 2020. Through a systematic process of paper selection and review, three central themes were identified, namely, 1) EFL teachers' understanding of CT and CT instruction; 2) EFL teachers' CT instructional models and strategies; and 3) the impacts of EFL teachers' CT instruction on students and themselves with various influencing factors at individual, interpersonal, and environmental levels. The review sheds light on the gap between the curriculum rhetoric and classroom reality due to the lack of attention to CT in current language teacher education. It also provides a critical analysis of the research methodologies adopted in the existing literature and outlines new directions for interested researchers in the fields of language teaching and teacher education.